Make your moment : the savvy woman's communication playbook for getting the success you want - Lim, Dion (McGraw-Hill, 2020)
Guiding you through what she has learned on the career battlefield and what it means for other working women today, the author takes you through the treacherous?and often entertaining?landscape of the modern workplace, covering virtually every situation youre likely to experience. --